Effect of Cajamarca creole pig lard as a dietary replacement for soybean and palm oils on the productive response and plasma metabolites of turkey - Quintana, Marx (2024)
The effect of three sources of lipids in the diet of fattening turkeys from the Hybrid Converter line on growth, carcass weight and blood metabolites were evaluated. A total of 90 43-day-old male turkeys were randomly distributed into 3 treatments, with 5 repetitions and 6 birds per group. The turkeys received isonutritional diets supplemented with Cajamarca Creole lard (MCCC), soybean oil (AS) or palm oil (AP). Turkeys aged 43 to 70 days with MCCC and AP had better body weight gain, lower feed consumption and better feed conversion (p<0.05) than those with the AS treatment; However, there were no differences between treatments during the finishing phase (71-98 days) nor in the total fattening period (43-98 days). The carcass weight in MCCC and AS was greater than in AP, in addition, they reduced (p<0.05) the relative weight of the liver and the percentage of abdominal fat compared to AP. Triglycerides and total cholesterol in blood were lower (p<0.05) in AS and MCCC than in AP, likewise, MCCC decreased (p<0.05) the malondialdehyde content in blood. It is concluded that MCCC in fattening turkeys from 43 to 98 days of age can replace AS and AP in the diet, since it does not generate negative effects or a decrease in the evaluated indicators.